De impact van digitalisering op de toeristische werkgelegenheid in het Brussels Hoofdstedelijk Gewest: een vooruitblik - Isabelle Cloquet; Cécile van de Leemput; Catherine Hellemans; Pierre Flandrin; Olivier Patris; Roxane Toumia (Brussels Studies, 2025)
This paper adopts a systemic approach in order to explore how digitalisation is likely to affect tourism employment in the tourist area of Brussels by 2030. Based on desk research and semi-structured interviews with 63 tourism stakeholders, it highlights the social and economic embeddedness of rationalising and restructuring work in tourism organisations. Digitalisation is and will continue to be used in the industry to increase productivity. This involves reducing costs, including human resources. Elements supporting this view include: the mode of reasoning centred on economics of tourism providers regarding digitalisation, their dependence on digital intermediaries which occupy a dominant position in the system, digitalisation-induced competition, price sensitivity of customers and costs of the human workforce, which is considered particularly high in Brussels. The system structures and institutions in the Brussels-Capital Region adapt to this trend and mitigate some of the effects of changes. Social structures also hinder adaptation of the tourism system and (future) workers, for instance in terms of education.